Preparation of high molecular weight atactic poly (vinyl alcohol) by the low temperature suspension polymerization of vinyl acetate - Lyoo, W.S.; Lee, S.G.; Lee, C.J. (1996)
To obtain high yield and high molecular weight poly(vinyl acetate) (PVAc) for a precusor of high molecular weight atactic poly(vinyl alcohol) (PVA), vinyl acetate (VAc) was suspension polymerized at 40 °C using a low temperature initiator, 2,2′-azobis (2,4-dimethylvaleronitrile) (ADMVN), and the effects of polymerization conditions on the polymerization behavior and molecular structure of PVAc, and PVA prepared by saponifying PVAc were studied. Lowering the polymerization temperature, implemented by using ADMVN, proved successful in obtaining PVA having number-average degree of polymerization (Pn) of over 3500. Moreover, maximum conversion of VAc into PVAc up to 96.3% (below 40% in the case of bulk polymerization of VAc at the same condition) was achieved. PVAc having Pn of 8000-15000 was obtained, and the degree of branching for acetyl group was ca. 1.5-3.5 at conversion of 50-95%. By saponifying the prepared PVAc, PVA having maximum Pn of over 4500 was obtained. The syndiotactic diad content of PVA was nearly constant ranging 51.5-52.5% and independent of the Pn of PVA.